Peran Komunikasi Yang Baik Dan Efektif Dalam Berorganisasi IPNU/IPPNU Di Desa Keboansikep - Manzilah Ar Rohmah; Wahyu Eko Pujianto (Jurnal Pengabdian Kepada Masyarakat, 2023)
This research explores the role of good and effective communication in the IPNU/IPPNU organization in Keboansikep Village. The research focus includes identity between members, quality of cooperation, and solidarity among organizational members. The research method involved interviews with IPNU/IPPNU members to understand their perceptions of the role of communication in the organization. The research results show that although there are efforts to maintain good communication, the existence of group differences can create pros and cons between members. To overcome these obstacles, research recommends regular activities such as meetings and joint sports activities between members. In addition, large activities such as Islamic New Year celebrations can be used to strengthen solidarity through uniting members from various groups. The main challenge in creating effective communication is differences of opinion during meetings, which can be overcome by finding the best solution through a majority vote mechanism. This research emphasizes the importance of good communication in avoiding the formation of groups and maintaining harmony within the IPNU/IPPNU organization. Therefore, routine activities and identification strategies between members are proposed as concrete steps to develop and maintain the sustainability of the organization.